Aspirin Derivatives Exploration: A Review on Comparison Study with Parent Drug - Hamdan, Azni Izwati; Nordin, Norsyafikah Asyilla; Sukmana, Dike Dandari (Iraqi Journal of Pharmaceutical Sciences, 2022)
In recent decades, drug modification is no longer unusual in the pharmaceutical world as living things are evolving in response to environmental changes. A non-steroidal anti-inflammatory drug (NSAID) such as aspirin is a common over-the-counter drug that can be purchased without medical prescription. Aspirin can inhibit the synthesis of prostaglandin by blocking the cyclooxygenase (COX) which contributes to its properties such as anti-inflammatory, antipyretic, antiplatelet and etc. It is also being considered as a chemopreventive agent due to its antithrombotic actions through the COX’s inhibition. However, the prolonged use of aspirin can cause heartburn, ulceration, and gastro-toxicity in children and adults. This review article highlights the recent derivatives of aspirin, either to reduce the risk of side effects or to obtain better physicochemical properties. Aspirin derivatives can be synthesized in various pathways and have been reported to give better biological activities such as anticancer, anti-inflammatory, antibacterial, antioxidant, etc., compared to the parent drug. The presence of significant moieties such as nitric oxide (NO), NOSH, thiourea, azo, amide, and chalcone on the modified aspirin play important roles in achieving desired biological activities. The addition of the halogen in the modification has also become a preference among researchers as it also affects the actions due to its ability to hinder bacterial activity. This review is also sharing about the bulkiness effect of certain aspirin modifications that may cause steric hindrance of the compounds and influence their penetration into the enzyme’s active site. Overall, these aspirin modifications are safe to be considered as potential pharmaceutical agents.